Sola Scriptura and the Evolutionary Argument Against Naturalism - Stacey, Gregory; McNabb, Tyler (TheoLogica: An International Journal for Philosophy of Religion and Philosophical Theology, 2025)
Inspired by Plantinga’s Evolutionary Argument Against Naturalism (EAAN), we develop an argument—the “Scriptural Argument Against Dogmatic Protestantism” (SAADP)—that Protestants who accept the doctrine of sola scriptura cannot reasonably hold that Catholic and Eastern churches are in doctrinal error. If sola scriptura is true and Catholic and Eastern Churches have fallen into error, it is improbable that any Protestant can reliably form true beliefs about controversial points of Christian doctrine, including sola scriptura or suggestions that Catholic and Eastern Christians are in error. We evaluate potential responses to SADDP, considering how SAADP should affect ecumenical doctrinal debates.